Pengaruh Perbedaan Model Irisan Stek Ubi Kayu dan Kemiringan Lereng terhadap Pertumbuhan dan Hasil Tanaman Ubi Kayu (Manihot esculenta Crantz) di Inceptisol Ternate - Banapon, Yulisa; Hartati, Tri Mulya; Abdurachman, Idris (Universitas Khairun, 2020)
Cassava (Manihot esculenta Crantz) has a strategic position as a material for food and non-food production, besides that, cassava is also a foreign exchange earner through the export of flour, starch and other processed products. The research objective was to determine the effect of different custtings and slope modelson the growth and yield of cassava plants. The research uses local varieties from Tobelo in the hope that it can support the national cassava. The study used a Divided Plot Design (RPT). The main plot is the slope of the slope (M) which consists of three levels, namely: M1 (slope 0-3%), M2 (slope 3-8%) and M3 (slope 8-15%) and as a sub-plot is the cuttings model L) which consists of three levels, namely: L1 (flat cuttings), L2 (one-sided tapered cuttings), and L3 (two-sided tapered cuttings. Parameters observed included plant height, number of leaves, stem diameter, leaf area, tuber length, tuber diameter, weight of cassava per hectare The results showed that the treatment had no signify cant effect either singly or in combination to the yield of cassava at harvest. The highest yield was found in the combination of M2L2 treatment, namely: 25 ton ha-1